HIV pre-exposure prophylaxis in transgender women: a subgroup analysis of the iPrEx trial. Issue 12 (December 2015) - Deutsch, Madeline B; Glidden, David V; Sevelius, Jae; Keatley, Joanne; McMahan, Vanessa; Guanira, Juan; Kallas, Esper G; Chariyalertsak, Suwat; Grant, Robert M; ,
Summary: Background: Pre-exposure prophylaxis (PrEP) with oral emtricitabine and tenofovir disoproxil fumarate is used to prevent the sexual acquisition of HIV in groups at high risk such as transgender women. We used data from the iPrEx study to assess PrEP efficacy, effectiveness, and adherence in transgender women. Methods: The iPrEx trial was a randomised controlled trial of PrEP with oral emtricitabine plus tenofovir disoproxil fumarate compared with placebo in men who have sex with men (MSM) and transgender women, followed by an open-label extension. Drug concentrations were measured in blood by liquid chromatography and tandem mass spectroscopy. We did unplanned exploratory analyses to investigate differences in PrEP outcomes among transgender women and between transgender women and MSM. Findings: Of the 2499 participants enrolled in the randomised controlled trial, 29 (1%) identified as women, 296 (12%) identified as trans, 14 (1%) identified as men but reported use of feminising hormones, such that 339 (14%) reported one or more characteristics and are classified as transgender women for the purpose of this study. Compared with MSM, transgender women more frequently reported transactional sex, receptive anal intercourse without a condom, or more than five partners in the past 3 months. Among transgender women, there were 11 HIV infections in the PrEP group and ten in the placebo group (hazard ratio 1·1, 95% CI 0·5–2·7). In the PrEP group, drug was detected in none of the transgender women at the seroconversion visit, six (18%) of 33 seronegative transgender women (p=0·31), and 58 (52%) of 111 seronegative MSM (p<0·0001). PrEP use was not linked to behavioural indicators of HIV risk among transgender women, whereas MSM at highest risk were more adherent. Interpretation: PrEP seems to be effective in preventing HIV acquisition in transgender women when taken, but there seem to be barriers to adherence, particularly among those at the most risk. Studies of PrEP use in transgender women populations should be designed and tailored specifically for this population, rather than adapted from or subsumed into studies of MSM. Funding: US National Institutes of Health and the Bill & Melinda Gates Foundation.